Produção de embriões bovinos in vitro com sêmen sexado - Araújo, Michelle Silva [UNESP]; Volpato, Rodrigo [UNESP]; Lopes, Maria Denise [UNESP] (My University, 2014)
The advent of sex-sorting-sperm sex selection of offspring became a great advantage, especially for dairy farms, which need new heifers for maintenance of his herds, and for beef cattle breeders, who crave more males for meat production. Currently, the only known technique capable of separating the populations of X and Y mammals sperm cells with efficiency and purity above 90% is flow cytometry. The best way of using sexed semen is in vitro fertilization, due to the small number of available sperm after sexing. Several factors can influence the results of in vitro embryos production using bovine sexed semen; among them there are the low rates of fertilization, cleavage, blastocyst, pregnancies, partially sperm capacitation, diluted semen samples and variation among bulls. Several studies have been conducted in order to assess the genetic and epigenetic alterations resulting from the use of sexed semen in the production of bovine embryos in vitro. Therefore, this paper aims to conduct a literature review on the limitations and advantages of using sexed semen, with emphasis on the technique of flow cytometry, during in vitro embryo production in cattle.

Com o advento da sexagem espermática a escolha do sexo da prole se tornou uma grande vantagem, principalmente para os criadores de gado leiteiro, que necessitam de novas matrizes para a manutenção do seu rebanho e para os criadores de gado de corte, que almejam mais machos para a produção de carne. Atualmente, a única técnica conhecida capaz de separar as popula- ções de espermatozoides X e Y de mamíferos, com eficiência e pureza acima de 90%, é a citometria de fluxo. A melhor forma de uso do sêmen sexado é na fertilização in vitro, devido ao reduzido número de espermatozoides disponíveis após a sexagem. Vários fatores podem influenciar os resultados da produção in vitro de embriões na espécie bovina utilizando sêmen sexado; dentre eles destacam-se as baixas taxas de fertilização, de clivagem, de blastocistos, de gestações; capacitação espermática parcial; amostras seminais diluídas e a variação entre touros. Alguns estudos têm sido realizados com o intuito de avaliar as alterações genéticas e epigenéticas decorrentes do uso do sêmen sexado na produção de embriões bovinos in vitro. Portanto, este trabalho tem como objetivo realizar uma revisão de literatura sobre as limitações e as vantagens do uso do sêmen sexado, com ênfase na técnica de citometria de fluxo, durante a produção embrionária in vitro na espécie bovina.
In vitro production of bovine embryos with sex-sorted semen
Keywords: Sexed semen; In vitro fertilization; Gene expression; Bovino; Sêmen sexado; Fertilização in vitro; Expressão gênica